An electron-optical system based on superconducting coil for a 670 GHz traveling wave tube - Junzhi Wang; Yi Jiang; Luqi Zhang; Xiuyuan Xu; Youhui He; Wenqiang Lei; Rui Song; Dimin Sun; Guowu Ma (AIP Advances)
This study proposes a novel electron-optical system (EOS) based on superconducting coils (SCs) for a 670 GHz traveling wave tube (TWT), demonstrating significant improvements in electron beam focusing capabilities. By utilizing magnetic field intensities significantly surpassing that of a permanent magnet, the electron beam is effectively compressed with the aim of achieving stable transmission of a current exceeding 30 mA through a channel with a diameter of 0.1 mm and a length of 100 mm. We developed and fabricated an electron gun operating at 23 kV with a current of 33 mA, aimed at assessing the feasibility of the SC EOS. In transmission experiments, we successfully obtained a collection electrode current approaching 24 mA, achieving an electron beam transmission rate of 76%. Furthermore, to assess the performance of the EOS, a preliminary design of a folded waveguide slow-wave structure for a 670 GHz TWT was developed. In the simulation analysis, an output power peak of 4.7 W at a frequency of 665 GHz was attained with an electron beam current of 30 mA.